The popular music and entertainment culture of Barbados : pathways to digital culture - Best, Curwen (Pathways to digital culture., 2012)
Curwen Best's The Popular Music and Entertainment Culture of Barbados surveys the development of Barbadian popular music and entertainment culture by focusing on pivotal phenomena, artists, and movements in the evolution of Barbadian popular music and culture. Best concentrates, in particular, on transformations since 1980 and 2000 respectively, each of which marked the ushering in of new opportunities and challenges to the creation and dissemination of Barbadian popular music.